TRANSPARENCY IN CORPORATE GOVERNANCE: ITS ROLE IN MITIGATING FINANCIAL RISKS AND IMPROVING PERFORMANCE METRICS - S, Thanigaimani; Reddy P, Shankar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In-depth analysis of the vital role that openness plays in corporate governance is provided in this paper, with particular attention to how it improves organizational performance measures and reduces financial risk. Transparent corporate governance processes are more important than ever in a time of growing complexity in global business operations and elevated stakeholder expectations. Using a mixed-methods approach, this study combines qualitative insights from in-depth interviews with business executives, regulators, and governance experts with quantitative analysis of financial data from 500 publicly traded companies across several industries. The study's five-year duration, from 2019 to 2023, enables a thorough analysis of trends and causal connections. Based on reduced stock price volatility, fewer substantial financial restatements, and improved credit ratings, our results show a clear positive association between more corporate transparency and better financial risk management. Additionally, the study shows that businesses with more open governance processes routinely beat their less open competitors on a number of important performance criteria, such as customer happiness, employee productivity, and return on equity (ROE). The study also reveals complex connections between particular transparency metrics and performance results, emphasizing the necessity of customized strategies for improving openness depending on organizational and industry-specific factors. These revelations aid in the creation of an all-encompassing framework for putting corporate transparency into practice and gauging its effectiveness, offering practitioners, legislators, and scholars studying corporate governance useful direction.